Sixth Five Year Plan 1980-85 Mid-Term Appraisal - Planning Commission, Government of India (Planning Commission, Government of India, 1980)
The Sixth Five Year Plan started in extremely difficult circumstances and had to contend with a number of unfavourable factors. The year 1979-80 witnessed a bad drought which affected agricultural production considerably. Food grain production recorded a heavy fall of 16.8 per cent compared to the previous year. There was an absolute decline in GDP of nearly 5 per cent. As a consequence, savings and investment went down significantly, thereby reducing the resources base of the Sixth Plan. In genera1, the economy was not in a very satisfactory state and the functioning of the infrastructure, in particular, had been badly affected. Against this background, the Sixth Plan was launched with a very ambitious programme of growth, poverty alleviation and self reliance.
Planning Commission Government of India
Planning Commission Government of India
Keywords: Sixth Five Year Plan- India; Economic Development